1990
DOI: 10.1080/01431169008955034
|View full text |Cite
|
Sign up to set email alerts
|

Digital processing of Landsat TM data for wasteland mapping in parts of Aligarh District (Uttar Pradesh), India

Abstract: Information on the spatial distribution of different wasteland categories forms a basic component in the large-scale reclamation and utilization programmes of these degraded lands. To evaluate the use of Landsat Thematic Mapper (TM) data in wasteland mapping, an attempt was made in this study to delineate and map various kinds of wastelands, in parts of Aligarh District (Uttar Pradesh) by digital analysis of Landsat TM data of 27 January 1986, using the maximum-likelihood classifier method. Map-to-image rectif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
2

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 3 publications
0
20
0
2
Order By: Relevance
“…The overall accuracy of 80% was achieved by this technique in this study. Saha et al (1990) also reported overall accuracy of 96% in wasteland classification of Aligarh district, U.P. India through digitally classifying Landsat TM data using maximum likelihood algorithm.…”
Section: Fig 3 Distribution Of Land Use and Vegetation Typesmentioning
confidence: 96%
“…The overall accuracy of 80% was achieved by this technique in this study. Saha et al (1990) also reported overall accuracy of 96% in wasteland classification of Aligarh district, U.P. India through digitally classifying Landsat TM data using maximum likelihood algorithm.…”
Section: Fig 3 Distribution Of Land Use and Vegetation Typesmentioning
confidence: 96%
“…Menenti et al (1986) found that Landsat 1 Thematic Mapper (TM) bands 1 through 5 and 7 were good for identifying salt minerals, at least when they are a dominant soil constituent. TM bands 3, 4, 5, and 7 were recommended for salt detection by Saha et al (1990) and Naseri (1998). Madrigal et al (2003) and Verma et al (1994) detected soil salinity of cropped areas by correlating soil EC determined at point sites within previously designated fields, to spectral values extracted from bands 2, 3 and 4 but integration of thermal band 6 headed to solve the problem of spectral similarity in the latter case.…”
Section: Soil Salinity Mapping and Monitoringmentioning
confidence: 99%
“…They indicated that using TM data along with aerial photographs for mapping soil in arid areas give valuable results. Reference [9] used bands 3, 4, 5, and 7 of TM data for mapping salt-affected and waterlogged areas in India. Reference [10] used False Colour Composite (FCC) of TM bands 2, 3 and 4 for visual interpretation of moderately and strongly sodic soils.…”
Section: A Remote Sensing Approach For Monitoringmentioning
confidence: 99%